EVALUATION OF THE ANTICANCER PROPERTIES OF TURMESAC® IN HUMAN CERVICAL ADENOCARCINOMA - HM, FIROZ; S, NANJUNDAIAH; CT, SADASHIVA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: In the current study, an extract of turmeric rhizome (Turmesac®) was evaluated for possible anticancer activity in human cervical adenocarcinoma (HeLa) cells. Methods: Turmesac®’s ability to elicit cytotoxicity in cancer cells was evaluated by (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay (MTT) assay, where the IC50 value was determined. Apoptosis induction and cell cycle arrest were analyzed by flow cytometry post-Turmesac® IC50 value treatment for 24 h. Results: The determined IC50 value of Turmesac® in HeLa cells was 115.12 μg/ml. This concentration was able to induce apoptosis 2 times greater than the apoptotic standard, camptothecin, treated cells. Cell cycle arrest was observed at the G0/G1 and S phases in Turmesac® treated HeLa cells. Conclusion: Turmesac® shows the potential of being a promising anticancer agent that may be incorporated into chemotherapies, but further study is required to elucidate the exact mechanisms involved with longer treatment duration, as would be the case in clinical trial phases.